2015
DOI: 10.1007/s10086-015-1527-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the width and lay-up of sugi cross-laminated timber (CLT) on its dynamic and static elastic moduli, and tensile strength

Abstract: Cross-laminated timber (CLT) has recently emerged as a new wood product that utilizes a large quantity of domestic lumber. This study aims to analyze the effects of width and lay-ups on the tensile strength of CLT. To this end, the elastic modulus of sugi CLT with different lay-ups was measured by dynamic and static methods. Moreover, tensile tests were conducted for different widths and lay-ups of CLT. Results indicate that the apparent bending Young's modulus, as calculated using the dynamic method, is direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 4 publications
(4 reference statements)
1
17
0
Order By: Relevance
“…They found that the bending creep performance perpendicular to the grain was improved by cross-lamination. The effects of width and lay-up on the tensile strength of CLT were studied by Ido et al [14]. The elastic modulus of CLT made of Sugi with different layups was measured by dynamic and static methods, and tensile tests were conducted for different widths and lay-ups.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the bending creep performance perpendicular to the grain was improved by cross-lamination. The effects of width and lay-up on the tensile strength of CLT were studied by Ido et al [14]. The elastic modulus of CLT made of Sugi with different layups was measured by dynamic and static methods, and tensile tests were conducted for different widths and lay-ups.…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al [8] proposed a lamina-property-based model for predicting the compressive strength of CLT panels, and revealed that the CLT compressive strength increased with an increase of the lamina number. Ido et al [9] analyzed the effects of width and layups on the CLT tensile strength, and found that the tensile strength calculated using the Young's modulus of the lamina of each layer was in agreement with the measured tensile strength.…”
Section: Introductionmentioning
confidence: 80%
“…Tensile strength predictions were evaluated for 74 test results of CLT specimens using the methods proposed by Unterwieser et al [16] (Eq. ( 4)) and Ido et al [7] (Eq. ( 8)).…”
Section: Weighted Averagementioning
confidence: 99%
“…3.2 Ido et al [7] for Tensile Strength Ido et al [7] conducted tensile strength tests on CLT samples by varying the cross-sectional width and the number of lamellae. Based on the test results conducted on CLTs made from Japanese Sugi, a new equation was proposed (Eq.…”
Section: Unterwieser Et Al [16] For Bending Tensile and Compressive Strengthmentioning
confidence: 99%
See 1 more Smart Citation